Pengaruh Online Customer Rating, Online Customer Review Dan Brand Ambassador Terhadap Minat Beli E-Commerce Shopee Pada Universitas Prima Indonesia (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The study's overarching goal was to ascertain how Universitas Prima Indonesian students' perceptions of online customer ratings, reviews, and brand ambassadors affected their propensity to use Shopee for online shopping. This study's population consists of all current Universitas Prima Indonesia students. Using the Non-Probability Sampling technique with Purposive samplings and certified Hair et al formula, a questionnaire was randomly distributed using gform to 100 respondents from Universitas Prima Indonesia for the sampling. The statistical package SPSS is used for data processing in this study, which employs dual linear regression. Universitas Prima Indonesian students' interest in purchasing from Shopee and other e-commerce platforms is positively and significantly impacted by brand ambassadors, online customer reviews, and variable online customer ratings.
Keywords: Online Customer Rating, Online Customer Review, Brand Ambassador, Buy Interest